Sustainable Warehouse Packaging: Environmental Impacts and Optimization Strategies - Vishnu Prasad Krishnakumar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the environmental impacts and optimization strategies in sustainable warehouse packaging, focusing on the integration of modern technologies and circular economy principles. The article investigates various aspects of warehouse sustainability, including material and energy efficiency, sustainable materials design, transportation optimization, and circular systems implementation. It explores how organizations can achieve both environmental responsibility and operational efficiency through strategic implementation of green practices. The article analyzes multiple dimensions of warehouse sustainability, from waste reduction strategies and eco-friendly alternatives to transportation optimization and reusable packaging solutions. Through examination of industry best practices and emerging trends, the article demonstrates how digital transformation, advanced analytics, and automated systems contribute to improved environmental performance while maintaining operational excellence. The article highlights the importance of integrating sustainability across the entire supply chain network, from material selection to end-of-life considerations, emphasizing the role of circular economy principles in creating resilient and environmentally responsible warehouse operations.
Keywords: Sustainable Warehouse Management; Environmental Optimization; Circular Economy; Green Logistics; Digital Transformation